Instilação de formalina endoluminal como opção terapêutica da retite actínica hemorrágica - Teixeira, Fábio Vieira [UNESP]; Denadai, Rafael; Ferraz, Rafael Aliceda; Goulart, Ricardo de Álvares; Saad-Hossne, Rogério [UNESP] (Cidade Editora Científica Ltda, 2011)
A retite actínica hemorrágica é um quadro grave que pode ocorrer em qualquer paciente submetido à radioterapia pélvica, por vezes, sendo necessária terapia transfusional e internação hospitalar. A abordagem terapêutica ainda é bastante controversa. Tanto para o tratamento inicial como para casos refratários, uma das opções é a aplicação de formalina. Este método é barato, facilmente disponível, de simples execução e eficaz no controle da hemorragia. Os autores relatam dois casos de retite actínica hemorrágica de pacientes tratados com instilação de formalina endoluminal, e sua eficácia terapêutica e complicações são discutidas

The radiation-induced hemorrhagic proctitis is a serious condition that can occur in any patient undergoing pelvic radiotherapy, sometimes being required hospitalization and transfusion therapy. The therapeutic approach is still very controversial. Both for the initial treatment and for refractory cases, one option is formalin application. This method is cheap, easily available, simple to perform, and effective in controlling bleeding. The authors report two cases of radiation-induced hemorrhagic proctitis treated with endoluminal instillation of formalin, and they discuss its therapeutic efficacy and complications
Endoluminal formalin instillation as a therapeutic option of radiation-induced hemorrhagic proctitis
Keywords: proctologia; colonoscopia; resultado de tratamento; formaldeído; proctology; colonoscopy; treatment outcome; formaldehyde